Students' perceptions, interaction and satisfaction in the interactive blended courses: A case study - Atici, Bünyamin; Türel, Yalin Kiliç (IGI Global, 2011)
Blended courses that offer several possibilities to students and teachers such as becoming more interactive and more active have become increasingly widespread for both K12 and higher education settings. With the rising of the cutting edge technologies, institutions and instructors have embarked on creating new learning environments with a variety of new delivery methods. At the same time, designing visually impressive and attractive blended settings for students has been easier with extensive learning and content management systems (LMS, CMS, LCMS) such as Blackboard, WebCT, Moodle and virtual classroom environments (VLE) such as Adobe Connect, Dimdim, and WiZiQ. In this study, the authors aimed to investigate students' perspectives and satisfactions towards designed interactive blended learning settings and to find out the students' views on both synchronous and asynchronous interactive blended learning environment (IBLE). © 2011 by IGI Global. All rights reserved.
Keywords: Computer aided instruction; Curricula; E-learning; Education computing; Learning systems; Teaching; Virtual reality; Case-studies; Cutting edge technology; Delivery methods; High educations; K-12 education; Learning environments; Student interactions; Student perceptions; Student satisfaction; Teachers'; Students